A utilização de mapas conceituais em uma atividade orientada para a promoção da argumentação científica escolar - Costa, Amanda Glycia Silva Moreira da (2021)
In the area of science teaching, the defenses for the use of teaching strategies are broadened with a view to the development of argumentative skills. Among the arguments they highlight the relationship with the formation of critical and reflective citizens. One of the strategies highlighted is the use of concept maps as a teaching tool for the promotion of argumentation. Which leads us to delimit our research question: “Activities oriented with the use of concept maps can promote the occurrence of argumentation in the classroom? If so, how? ”. From this question, we intend to identify manifestations of argument supported by data in processes of defense and refutation of conceptual maps in the context of activities guided by scripts in the classroom. To this end, we planned a sequence of activities on the theme “acid rain” involving the process of building, reformulating and defending concept maps. Guiding scripts were prepared for all stages. The intervention took place in 5 meetings in the discipline of Chemistry with students from the technical course integrated at the medium level in Informatics at IFRN, Campus Currais Novos (CAAE - Certificate of Presentation of Ethical Appreciation, no. 15863319.3.0000.5537). Data collection was performed by recording (audio and video) the speeches during the debate of concept maps. For the analysis of the data, the rubric of the authors Shemwell and Furtak (2009) was adapted, which addressed the following points: the absence of data, the use of data and the articulation of data with conceptual relationships. The data correspond to the elements that make up a conceptual map (terms of connection, arrows, concepts, propositions, among others) and the conceptual relationships are the information of a scientific school character, used to support the students' statements. As main results we highlight that the students presented, during the defense of concept maps, statements using data and articulating them with the concepts. We conclude that the inclusion of this stage revealed the potential to promote the negotiation of meanings, scientific argumentation in the classroom and the evaluation of their own conceptions.